Intracranial Otogenic Complications in Adults: New Factors That Influence its Onset - Mohammad Qamar Nasir, Ruqqiya Saadat, Syed Umair Iftikhar, Abdul Shakoor, Ameer Humza, Hassan Majid Bhatti (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate new factors which influence intracranial otogenic complications in adults. Study Design: Retrospective study Place and duration of study: Department of ENT, Services Hospital Lahore from 1st October 2021 to 31st March 2022. Methodology: Fifty patients were analyzed in COVID times (2020-2021) with intracranial otogenic complications for determination of new factors for the onset of this disease complication. Hundred patients were assessed from the time period of 2014-2018. The diagnosis was confirmed on the basis of MRI or MRV imaging with intracranial complications. Reverse Transcriptase PCR was also performed on each patient through naso-pharyngeal swab test. The patients age, gender, clinical and comorbidity history, neurological state, immobility, prophylaxis and coagulopathy risks were documented. Result: The mean age of the patients was 62.3±5.5 years during COVID times and 50.2±6.1 years before COVID-19. The Pre-COVID-19 period had all males reported with intracranial otogenic complications. While in COVID times 12% females were reported with intracranial otogenic complications such as meningitis, brain abscess as well as Lateral/venous sinus thrombosis. Lateral/venous sinus thrombosis among IOC was more commonly observed in the COVID time. Conclusion: Cerebral lateral/venous-sinus thrombosis is appeared to be the rare factor that can be linked with COVID-19. Keywords: Complications, Otitis media, COVID-19, Adult, Intracranial otitis